2009
DOI: 10.1542/peds.2009-1100d
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities Beginning in Childhood: A Life-Course Perspective

Abstract: In this article we argue for the utility of the life-course perspective as a tool for understanding and addressing health disparities across socioeconomic and racial or ethnic groups, particularly disparities that originate in childhood. Key concepts and terms used in life-course research are briefly defined; as resources, examples of existing literature and the outcomes covered are provided along with examples of longitudinal databases that have often been used for life-course research. The life-course perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
367
2
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(396 citation statements)
references
References 99 publications
17
367
2
10
Order By: Relevance
“…[3][4][5] Although new discoveries in basic science, clinical subspecialties, and high-technology medical interventions continue to advance our capacity to treat patients who are ill, there is growing appreciation that a successful well-care system must expand its scope beyond the traditional realm of individualized, clinical practice to address the complex social, economic, cultural, environmental, and developmental influences that lead to population-based health disparities and unsustainable medical care expenditures. 2,6,7 The science of early childhood development has much to offer in the realization of this vision, and the well-being of young children and their families is emerging as a promising focus for creative investment.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Although new discoveries in basic science, clinical subspecialties, and high-technology medical interventions continue to advance our capacity to treat patients who are ill, there is growing appreciation that a successful well-care system must expand its scope beyond the traditional realm of individualized, clinical practice to address the complex social, economic, cultural, environmental, and developmental influences that lead to population-based health disparities and unsustainable medical care expenditures. 2,6,7 The science of early childhood development has much to offer in the realization of this vision, and the well-being of young children and their families is emerging as a promising focus for creative investment.…”
Section: Introductionmentioning
confidence: 99%
“…A loss may be particularly consequential if it occurs earlier in the life course than expected (28)(29)(30). For example, the death of a parent in childhood is particularly likely to trigger biopsychosocial sequelae that undermine health (9,(29)(30)(31)(32). Off-time losses in adulthood-such as losing a spouse as a young adult-may also have a more pronounced impact (4,33).…”
mentioning
confidence: 99%
“…Previous literature identified the carer's depression scale, carer's health behaviour, SEP, and neighbourhood characteristics as significant predictors for concurrent health outcome [5,6,10], as well as for a longer lasting effect on later adult health [5,6,[8][9][10]28]. The literature also showed that excessive consumption of alcohol or cigarettes among Indigenous carers, to some extent, led to financial or depression problems and resulted in poor care for their children [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Our study was based on the life-course epidemiology concept [28,[35][36][37]. The life-course perspective concentrates on understanding early-life experiences and how they can shape health across an entire lifetime and potentially across generations by systematically concentrating on the role of context, including the social and physical context along with biological factors, over time.…”
Section: Discussionmentioning
confidence: 99%